2008
DOI: 10.1155/2008/953692
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of tiron as scavenger of superoxide ions and free electrons

Abstract: Sodium 4,5-dihydroxybenzene-1,3-disulfonate (tiron) has been reported to be an efficient chelator of certain metal ions, and a substrate in several enzyme reactions. Its small size facilitates cell entry and therefore modulates intracellular electron transfer reactions as an antioxidant by scavenging free radicals. Its reduction by electrochemical and enzymatic methods gives identical products; a semiquinone detectable by EPR spectroscopy. In a test of its use as a spin trap, in comparison with DMPO, tiron doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…Tiron and Mn(III)tetrakis(4-benzoic acid)porphyrin (MnTBAP), which act as superoxide reducing agents (Ledenev et al, 1986) or inhibit superoxide formation (Taiwo, 2008), completely blocked rapid bacterial death (Figure 5D). Trolox, an α-tocopherol derivative that scavenges free radicals, the hydrogen peroxide scavenger DMTU and the iron-chelator deferoxamine also reduced bacteria killing, but less than Tiron or MnTBAP, providing further evidence that superoxide anion is the first ROS species produced.…”
Section: Resultsmentioning
confidence: 98%
“…Tiron and Mn(III)tetrakis(4-benzoic acid)porphyrin (MnTBAP), which act as superoxide reducing agents (Ledenev et al, 1986) or inhibit superoxide formation (Taiwo, 2008), completely blocked rapid bacterial death (Figure 5D). Trolox, an α-tocopherol derivative that scavenges free radicals, the hydrogen peroxide scavenger DMTU and the iron-chelator deferoxamine also reduced bacteria killing, but less than Tiron or MnTBAP, providing further evidence that superoxide anion is the first ROS species produced.…”
Section: Resultsmentioning
confidence: 98%
“…We found that COPD lung tissue has much higher levels of nitrotyrosine and 8-HG residues when compared with controls (indicating greater oxidative stress in the COPD samples), that NEP activity is directly inactivated by H 2 O 2 (which models the response of NEP to a number of oxidants in general), and that an antioxidant (tiron) prevents loss of NEP activity due to CSE, hypoxia, or H 2 O 2 , further strengthening this connection between reduced NEP activity and ROS in COPD. Although tiron acts as an SOD mimetic, it also is able to chelate certain metal ions, and has been shown to react with (''scavenge'') hydroxyl radicals (which are likely the major reactive species through which H 2 O 2 acts) at 100 times the rate that it reacts with superoxide radicals; tiron has been characterized as an electron trap (58). A preliminary experiment with other antioxidants with catalase-like activity suggests that, like these other antioxidants, in our experimental systems, tiron is able to combat oxidation by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ROS was measured to investigate the increased COX activity upon addition of ALA (Fig 5B). The changes in the amount of ROS were also determined when Tiron was added as a ROS scavenger [32,33]. ROS increased significantly after addition of ALA and/or SFC and was markedly suppressed under conditions where Tiron was added.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of COX in MKN45 cells by ALA+SFC (Fig 4) indicated that the leakage of superoxide anions from mitochondria most probably led to increased ROS (Fig 5). We used Tiron, an analog of vitamin E and a radical scavenger, as a ROS scavenger [32,33]. Tiron reduced ROS levels and showed recovery of cell proliferation (Fig 5).…”
Section: Discussionmentioning
confidence: 99%